Two new species of Pleurothallis (Orchidaceae: Pleurothallidinae) from Costa Rica in the P. phyllocardia group - Pupulin, Franco; Díaz-Morales, Melissa; Fernández, Melania; Aguilar, Jaime (Lankesteriana: International Journal on Orchidology, 2017)
Two new species of Pleurothallis subsection Macrophyllae-Fasciculatae from Costa Rica are described and illustrated, and their relationships discussed. Pleurothallis pudica, from the central Pacific mountain region, is compared with P. phyllocardia, but it is easily recognized by the densely pubescent- hirsute flowers. Pleurothallis luna-crescens, from the Caribbean slope of the Talamanca chain, is compared with P. radula and P. rectipetala, from which it is distinguished by the dark purple flowers and the distinctly longer, dentate petals, respectively. A key to the species of the group in Costa Rica and western Panama is presented.